BALANCED FORMS OF INNOVATIVE DEVELOPMENT ORGANIZATIONS - Pavel Timoshenko; Larissa Gorbenko (Вестник Северо-Кавказского федерального университета)
In article showing forms of balanced nature in the organization's management system, Specific character of display balanced nature in management, economics and finance, The structure offorms a balanced nature.